Aplikasi Penimbangan Balita Berbasis Internet Of Things (IoT) Untuk Meningkatkan Layanan Posyandu - Rully Pramudita; Muhammad Faisal (Jurnal ICT : Information Communication & Technology, 2021)
One of the services at the posyandu is weighing toddlers. But sometimes there is still a lack of accuracy in the measurement results. Therefore, in this study, designed and realized something that can measure body weight and provide information accurately and connected to a database. The software development method used in this research is the prototype method which supports the stages of making a prototype product before it becomes the final result. This measuring tool uses Arduino Uno as a microcontroller board, loadcell sensor to measure weight, and RFID to detect toddler's self data. The data from the two sensors is processed by Arduino Uno to be input into the database, the toddler's weight will be displayed on the LCD and sensor data will be displayed on the monitoring website. The results of the blackbox test of this system indicate that the tool can function properly